PENGEMBANGAN MEDIA ULAR TANGGA MENGGUNAKAN METODE TANYA JAWAB PADA PEMBELAJARAN MATEMATIKA MATERI PERKALIAN KELAS II SDN 11 SITIUNG KABUPATEN DHARMASRAYA - Nurlaila; Firman; Desyandri (STKIP Subang, 2024)
method to improve students' understanding of multiplication in mathematics. The research uses the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. The analysis phase identifies the need for interactive media that engages students and overcomes the boredom associated with traditional learning methods. During the design phase, the media is tailored to the characteristics of second-grade students, with a focus on color and simple multiplication questions. The development phase includes validation by experts, resulting in a product deemed highly valid. In the implementation phase, the media is tested in classrooms, showing positive feedback from both students and teachers, indicating that it is practical and effective in enhancing students' learning outcomes. The evaluation phase confirms the media's validity, practicality, and effectiveness in improving students' understanding of multiplication, offering valuable contributions to educational media development.